Penerapan Metode Agile Scrum Pada Perancangan Aplikasi Mobile MBKM-Report Di Universitas Putra Indonesia YPTK Padang - Zulkarnain; Musfiza, Efelito Hayat; Janata, Adit Afandi (Riset Sinergi Indonesia (RISINDO), 2024)
This research examines the application of the Agile Scrum method in developing the MBKM Report mobile application at Universitas Putra Indonesia YPTK Padang. Agile Scrum was chosen because of its ability to adapt to changes quickly and increase interaction between application users and the development team. This research applies a qualitative descriptive method with data collection techniques through observation, interviews and literature study. The initial development stage starts from needs analysis, design using Unified Modeling Language (UML), to application implementation and testing. The research results show that Agile Scrum can improve the quality of applications and the efficiency of the resulting development process. It is believed that the implementation of the MBKM Report application can speed up the process of reporting and monitoring MBKM activities and improve academic services at Universitas Putra Indonesia YPTK Padang